High-performance slow-curing polyurea compositions - S. V. Romanov; O. A. Botvinova; E. A. Timakov; D. A. Rashchupkina; Yu. T. Panov (Тонкие химические технологии)
Objectives. To improve the technology for obtaining polymer spray coatings based on polycarbodiimides (polyureas) by studying changes in the process and operational parameters due to the introduction of aspartic acid derivatives (AADs) into the composition.Methods. The process of the production of sprayed and contact polyureas involves a number of difficulties, not least in terms of the cost of the components and high-pressure equipment. For this reason, mathematical modeling was used to optimize experimental design. The curing time of the composition was measured under conditions simulated to be close to actual. After thermostating and mixing Components A and B in predetermined ratios, the gelation time was measured to represent the curing time of the composition. The hardness of the material was determined by the Shore method according to GOST 24621-91. Tensile strength and relative elongation were determined according to a standard method (GOST 30436-96).Results. The effect of three AADs on the properties of the finished polyurea was studied. It was found that the introduction of two of them (AAD-1 and AAD-2) into polyurea in an amount of up to 40 wt % produces slow-curing (>250 s) polyureas capable of manual application. The finished products have physical properties on par with machine-poured materials (breaking strength >73 MPa; tensile strength >23 MPa; elongation >500%). Compiled regression equations were used to construct graphs of equal levels showing the possible areas of directed modification of the studied compositions.Conclusions. AAD can be used as a modifying component for polyurea systems to obtain slow-curing polyureas with high performance properties, which can be purposefully controlled by mathematical modeling. The resulting products have commercial value due to their combination of valuable physical and mechanical properties.